Tau (MAPT) haplotypes in Jordan: new evidence on the Middle East as a melting-pot predating Neolithic migration - Almuthanna K. Alkaraki; Alanoud I. Abuelezz; Omar F. Khabour; Jose A. Peña; Miguel A. Alfonso-Sánchez; Zaid Altaany (Taylor & Francis Group, 2021)
Frequencies of H1 and H2 haplotypes of the microtubule-associated protein tau (MAPT) gene were examined in two Jordanian samples. The criterion for haplotype assignment was the presence/absence of the intronic 238-bp deletion, located between exons 9 and 10 of the MAPT genomic region. We further compiled MAPT haplotype frequencies in Middle Eastern, South Asian, and European populations to widen the scope of analyses. Jordan MAPT*H2 haplotype frequencies peaked among worldwide samples analysed to date, with the Jordan general population featuring the top value (0.386). AMOVA tests results indicated spatial genetic structuring, as they unveiled significant differences in H2 frequencies between South Asia and Europe, with a hypothetical contact zone in the Middle East. The southeastern region of the Middle East shares low H2 frequencies with South Asia, while the northwestern area shows high H2 frequencies, similar to and even higher than observed in Europe. We suggest that high H2 frequencies could have originated at the beginning of the Neolithic in the western region of the Middle East, most likely through genetic drift episodes associated with founding events. Subsequently, the arrival of Neolithic farmers boosted the H2 haplotype spreading throughout Europe.